Nanocoatings on micro- or nano-particles - Libor, Zsuzsanna; Zhang, Qi; Israel, C.; Mathur, N. D. (Maney Publishing, 2009)
In recent years, coating processes with nanoparticles have been investigated for the development of nanostructured materials. In this work we report the core-shell structures of micro-composites of SiO2/Ni, SiO2/Fe3O4, and nano-composites of BaTiO3/Fe3O4 and PZT/Fe3O4. These composites were prepared by an aqueous chemical synthesis method and characterised by scanning electron microscopy (SEM), X-ray diffraction (XRD), Energy Dispersive X-Ray (EDX) analysis and Vibrating Sample Magnetometry (VSM) before and after incorporation into the core-shell structure. The composite core-shell structures were formed by the control of the surface charges of particles in aqueous solutions. A specific composite (SiO2/Ni, SiO2/Fe3O4 and BaTiO3/Fe3O4 and PZT/Fe3O4 nano-composites) can be produced by controlling the pH and the molar ratio of components. These magnetic composites can be potentially applied in wide range of fields such as micro-reactors, delivery vehicle systems, drug delivery systems and multiferroics.
Keywords: Sol-gel processes; Nanocomposites; Magnetic properties; PZT; Core shell structure